Effect of PVD film's residual stresses on their mechanical properties, brittleness, adhesion and cutting performance of coated tools. (August 2017) - Skordaris, G.; Bouzakis, K.D.; Kotsanis, T.; Charalampous, P.; Bouzakis, E.; Breidenstein, B.; Bergmann, B.; Denkena, B.
Highlights: Cutting tools were coated with PVD films by applying diverse substrate bias voltages. In this way, the coated inserts possess various film residual stress distributions. The coating's mechanical properties were determined via innovative test methods. The raise in residual stresses enlarges not proportionally the coated tool life. Hereupon, a certain residual stress level can be considered as optimum. Abstract: Coated cemented carbide inserts with diverse compressive residual stresses in the film structure were manufactured applying different substrate bias voltages. Moreover, a portion of the coated specimens was annealed for eliminating compressive residual stresses. Residual stress measurements, nanoindentations, nano- and inclined-impact tests, as well as FEM-supported calculations were performed for assessing the coating's mechanical properties, cohesion, brittleness and adhesion. Furthermore, the cutting performance of the coated inserts was investigated in turning AISI 1045. According to the attained results, coating residual stresses affect significantly the film properties and wear behavior. Hereupon, a certain residual stress level can be considered as optimum.